Photocatalytic material of lead-rich halide perovskite bonded molybdenum disulfide as well as synthesis method and application of photocatalytic material

By generating strong lead-sulfur bonded lead-rich halide perovskite bonds on the surface of halide perovskite, the problem of low catalytic activity of halide perovskite is solved in decomposition of hydrohalogenic acid, and the problem of low catalytic activity of halide perovskite is achieved. It can produce hydrogen by efficient photocatalytic decomposition of hydrogen halogen acid and improve stability.

CN119237007AActive Publication Date: 2025-01-03GUANGDONG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411106155.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2025-01-03
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

The existing halide perovskite photocatalytic materials have low catalytic activity when decomposing hydrogen halogen acid, and low carrier separation and transmission efficiency, which limits their photocatalytic efficiency.

Method used

The photocatalytic material with lead-rich halide perovskite bonded with molybdenum disulfide is used to form strong lead-sulfur bonds on the surface and adjust the proportion of synthetic raw materials by synthesising it by saturated solution co-precipitation method to form a rich lead site close to molybdenum disulfide Contact promotes carrier separation and transmission.

Benefits of technology

Highly efficient photocatalytic decomposition of hydrogen halide acid is achieved, with high catalytic activity and stability, and the hydrogen production performance reaches 14,000 μmol g-1h-1, and the stability of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237007A_ABST
    Figure CN119237007A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new energy and photocatalysis, in particular to a photocatalytic material with lead-rich halide perovskite bonded with molybdenum disulfide as well as a synthesis method and application of the photocatalytic material with the lead-rich halide perovskite bonded with the molybdenum disulfide bonded with the lead-rich halide perovskite bonded with the molybdenum disulfide bonded with the lead-rich halide perovskite bonded with the molybdenum disulfide bonded with the molybdenum disulfide bonded with the lead-rich halide perovskite bonded with the molybdenum disulfide bonded with the molybdenum disulfide bonded with the molybdenum disulfide. The formamidine lead halide perovskite with abundant lead sites on the surface is synthesized by adopting a saturated solution coprecipitation method, and then the abundant lead sites exposed on the surface of the formamidine lead halide perovskite are in close contact with sulfur ions in a promoter molybdenum disulfide and are bonded to form stable lead-sulfur bonds; and the formed interface strong chemical bond greatly promotes the separation and transmission of current carriers, so that the synthesized photocatalytic material can realize high-efficiency photocatalytic decomposition of haloid acid for hydrogen production. The synthesis method of the photocatalytic material has the advantages of simple preparation method, mild reaction conditions, low cost and large-scale preparation, and the synthesized photocatalytic material has the advantage of high catalytic activity and has the advantage of high hydrogen production activity when being applied to photocatalytic hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy and photocatalytic technology, and in particular to a lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic material, a synthesis method and application thereof. Background Art

[0002] As a clean, high-energy-density and renewable energy, hydrogen will play an important role in the future energy structure. Hydrogen production through water splitting is considered to be one of the most environmentally friendly and sustainable strategies. Due to the large energy barrier of water splitting, the conversion efficiency of solar energy into hydrogen energy in current research is far lower than commercial requirements.

[0003] In addition, halide perovskites have excellent photoelectric properties such as narrow and appropriate band gaps, high absorption coefficients, and long carrier diffusion lengths, making them ideal photocatalytic materials. At the same time, the use of halide perovskite photocatalysts to catalyze the cracking of hydrohalic acid (HX, X = Br-, I-) to produce hydrogen makes it easier to convert solar energy into hydrogen energy, which provides a promising new path to replace water decomposition to produce hydrogen. This can not only realize the conversion of solar energy into hydrogen energy, but also can be coupled with hydrogen-halide liquid flow batteries as a charging reaction, so it is of great significance for solar energy collection, storage, and conversion into chemical energy and electrical energy.

[0004] However, in current research, the photocatalytic hydrogen evolution activity of decomposing hydrogen halides is still low, and the photogenerated carriers generated by halide perovskite photocatalysis cannot be effectively separated and transmitted, which greatly restricts its photocatalytic efficiency. Although researchers have improved the photocatalytic efficiency by modifying halide perovskites through component regulation, surface loading, and heterojunction construction, these modifications have limited effect on improving the photocatalytic efficiency due to the lack of effective reaction sites on the surface of halide perovskites, and cannot release the photocatalytic potential of halide perovskites. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the first object of the present invention is to provide a method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide. The synthesis method has the advantages of simple method, mild reaction conditions, low cost, and large-scale preparation, and the synthesized photocatalytic material has the advantage of high catalytic activity.

[0006] The second object of the present invention is to provide a lead-rich halide perovskite bonded molybdenum disulfide photocatalytic material, which can generate strong lead-sulfur bonds on the surface, has excellent stability, and has the advantages of efficient charge separation, abundant hydrogen production active sites and a smaller HX splitting energy barrier.

[0007] The third object of the present invention is to provide an application of a lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic material, which can be applied to photocatalytic hydrogen production and has efficient and stable photocatalytic hydrogen production activity.

[0008] In order to achieve the first object of the above invention, the technical solution adopted by the present invention is as follows:

[0009] The present invention provides a method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, comprising the following steps:

[0010] S1. Synthesis of halogenated formamidine: adding acetic acid formamidine to a hydrohalic acid solution for ultrasonic dispersion and then heating and stirring for reaction, then removing the solvent, washing and drying to obtain halogenated formamidine;

[0011] S2, preparation of formamidinium lead halide perovskite and saturated mixed acid solution: adding the excess formamidinium halide and lead halide obtained in step S1 to a mixed acid solution composed of a hydrohalic acid and a hypophosphorous acid solution, heating and stirring the mixture for reaction, cooling the mixture, and centrifuging the mixture for solid-liquid separation to obtain formamidinium lead halide perovskite and a saturated mixed acid solution;

[0012] S3, preparation of molybdenum disulfide: adding molybdate and sulfur source into water, stirring and dissolving, carrying out hydrothermal reaction, centrifuging, washing and drying to obtain molybdenum disulfide;

[0013] S4. Synthesis of photocatalytic material: Add the lead guanidine halide perovskite synthesized in step S2 and the molybdenum disulfide prepared in step S3 to the saturated mixed acid solution obtained in step S2 for heating and stirring reaction, and then cool, centrifuge and dry to obtain the FAPbX3 / MoS2 photocatalytic material, which is the lead-rich halide perovskite bonded with molybdenum disulfide photocatalytic material.

[0014] The saturated mixed acid solution obtained in step S2 is a mixed acid solution in which formamidinium lead halide perovskite is saturated with the solution.

[0015] The invention discloses a method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, wherein the ratio of the synthetic raw materials of formamidine halide, lead halide and mixed acid solution is adjusted, and a formamidine lead halide perovskite with rich lead sites on the surface is synthesized by a saturated solution coprecipitation method, and then the rich lead sites exposed on the surface of the formamidine lead halide perovskite are closely contacted with sulfur ions in the co-catalyst molybdenum disulfide, and bonded to form a stable lead-sulfur bond, and the formed strong chemical bond on the interface greatly promotes the separation and transmission of charge carriers, so that the synthesized photocatalytic material can realize efficient photocatalytic decomposition of halogen acid to produce hydrogen. The method for synthesizing the photocatalytic material has the advantages of simple preparation method, mild reaction conditions, low cost, and large-scale preparation, and the synthesized photocatalytic material has the advantages of high catalytic activity.

[0016] Furthermore, in step S1, the mass volume ratio of the acetic acid formamidine to the hydrohalic acid solution is 1 g: (1.5-2) mL; and / or

[0017] The mass concentration of the hydrohalic acid solution is 45% to 48%; and / or

[0018] The hydrohalic acid solution includes one or a combination of hydrobromic acid or hydroiodic acid.

[0019] Furthermore, in the step S1, the ultrasonic dispersion time is 5 min to 15 min, the heating temperature is 55° C. to 65° C., and the reaction time is 1.5 h to 2.5 h.

[0020] Further, in step S2, the molar ratio of the formamidine halide to the lead halide is (0.7-0.95):1; and / or

[0021] The mass volume ratio of the halogenated formamidine to the mixed acid solution is (3-10) g: (50-100) mL; and / or

[0022] In the mixed solution of the hydrohalic acid and the hypophosphorous acid solution, the volume ratio of the hydrohalic acid to the hypophosphorous acid solution is 4:(0.5-1); and / or

[0023] The heating temperature is 60° C. to 80° C., and the reaction time is 1 h to 1.5 h.

[0024] Further, in step S3, the molybdate is sodium molybdate or potassium molybdate, or a combination of both; and / or

[0025] The sulfur source is one or a combination of thioacetamide or thiourea; and / or

[0026] The molar ratio of the molybdate to the sulfur source is 1:(6-8); or / or

[0027] The temperature of the hydrothermal reaction is 180° C. to 220° C., and the time of the hydrothermal reaction is 20 h to 28 h.

[0028] Further, in step S4, the mass ratio of the formamidinium lead halide perovskite to molybdenum disulfide is (2.5-100):1; and / or

[0029] The mass concentration of the formamidinium lead halide perovskite in the saturated mixed acid solution is 1 g / L to 4 g / L; and / or

[0030] The temperature of the heating reaction is 50° C. to 80° C., and the reaction time is 1.5 h to 2.5 h.

[0031] In order to achieve the second purpose of the above invention, the technical solution adopted by the present invention is as follows:

[0032] The present invention provides a lead-rich halide perovskite bonded molybdenum disulfide photocatalytic material, which is prepared by the above-mentioned method for synthesizing the lead-rich halide perovskite bonded molybdenum disulfide photocatalytic material.

[0033] The photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide of the present invention has the advantages of efficient charge separation, abundant hydrogen production active sites, and small hydrohalic acid splitting energy barrier, and can realize efficient and stable photocatalytic hydrogen production, and the optimal hydrogen production performance is as high as 14000 μmol g -1 h -1 , while having excellent stability.

[0034] In order to achieve the third purpose of the above invention, the technical solution adopted by the present invention is as follows:

[0035] The invention provides an application of a lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic material in photocatalytic decomposition of halogen acid to produce hydrogen.

[0036] The photocatalytic material can be used for photocatalytic hydrogen production and has efficient and stable photocatalytic hydrogen production activity.

[0037] The present invention provides a method for producing hydrogen by photocatalytically decomposing halogen acid, which is a method for producing hydrogen by photocatalytically decomposing halogen acid using the above-mentioned lead-rich halide perovskite bonded molybdenum disulfide photocatalytic material, comprising the following steps: dispersing the photocatalytic material in the saturated mixed acid solution, vacuuming to remove air, and using a xenon lamp as a light source to photocatalytically decompose the halogen acid in the saturated mixed acid solution to produce hydrogen.

[0038] Furthermore, the mass volume ratio of the photocatalytic material to the saturated mixed acid solution is (1-5) mg: 1 mL; and / or

[0039] The power of the xenon lamp is 250W to 350W. The xenon lamp is equipped with filters of AM 1.5 and 420<λ<780nm.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, wherein the ratio of the synthetic raw materials of formamidine halide, lead halide and mixed acid solution is adjusted, and a saturated solution coprecipitation method is used to synthesize formamidine lead halide perovskite with rich lead sites on the surface, and then the rich lead sites exposed on the surface of the formamidine lead halide perovskite are closely contacted with sulfur ions in the co-catalyst molybdenum disulfide, and bonded to form a stable lead-sulfur bond, and the formed strong interfacial chemical bond greatly promotes the separation and transmission of carriers, so that the synthesized photocatalytic material can achieve efficient photocatalytic decomposition of hydrohalic acid to produce hydrogen. The method for synthesizing the photocatalytic material has the advantages of simple preparation method, mild reaction conditions, low cost, and large-scale preparation, and the synthesized photocatalytic material has the advantages of high catalytic activity.

[0042] (2) The lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic material of the present invention has the advantages of efficient charge separation, abundant hydrogen production active sites, and small hydrohalic acid splitting energy barrier, and can achieve efficient and stable photocatalytic hydrogen production, with the optimal hydrogen production performance reaching up to 14000 μmol g -1 h -1 , and at the same time has excellent stability due to the chemically bonded co-catalyst molybdenum disulfide.

[0043] (3) The present invention relates to an application of a lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic material in the photocatalytic decomposition of halogen acid to produce hydrogen. The photocatalytic material can be applied to photocatalytic hydrogen production, and because the photocatalytic material loads more co-catalyst molybdenum disulfide through strong lead-sulfur bonds, more reaction sites are generated, the separation and transmission efficiency of photogenerated carriers are enhanced, and the photocatalytic performance of the halide perovskite can be effectively improved. Therefore, the photocatalytic material has efficient and stable photocatalytic hydrogen production activity when applied to photocatalytic hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1 It is the X-ray powder diffraction pattern of the formamidinium lead halide perovskite prepared in Examples 1 to 3 and Comparative Examples 1 to 2 of the present invention.

[0046] Figure 2 It is the ultraviolet-visible light absorption spectrum diagram of the formamidinium lead halide perovskite prepared in Examples 1 to 3 and Comparative Examples 1 to 2 of the present invention.

[0047] Figure 3 It is the zeta potential diagram of the lead guanidine halide perovskite prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 and the molybdenum disulfide of Example 1.

[0048] Figure 4 This is a scanning electron microscope energy scattering element distribution diagram of the formamidinium lead halide perovskite prepared in Example 1 of the present invention.

[0049] Figure 5 It is the X-ray powder diffraction pattern of FAPbBr3-0.9, MoS2, and 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 of the present invention.

[0050] Figure 6 These are the UV-visible absorption spectra and optical photographs of FAPbBr3-0.9, MoS2, and 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 of the present invention. Figure 6 In the figure, the real optical photographs on the lower left refer to 20%MoS2 / FAPbBr3-0.9, FAPbBr3-0.9, and MoS2 from top to bottom.

[0051] Figure 7 This is a scanning electron microscope image of FAPbBr3-0.9 prepared in Example 1 of the present invention.

[0052] Figure 8 This is a scanning electron microscope image of 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 of the present invention.

[0053] Fig. 9 This is a scanning electron microscope energy scattering element distribution diagram of 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 of the present invention.

[0054] Fig.10 It is the infrared spectra of FAPbBr3-0.9, MoS2, and 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 of the present invention.

[0055] Fig.11 It is the Raman spectra of FAPbBr3-0.9, MoS2, and 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 of the present invention.

[0056] Fig.12 This is the bromine element spectrum in the X-ray photoelectron spectrum of FAPbBr3-0.9 and 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 of the present invention.

[0057] Fig.13This is the molybdenum element spectrum in the X-ray photoelectron spectrum of MoS2 and 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 of the present invention.

[0058] Fig.14 It is the photocatalytic hydrogen production activity diagram of 20% MoS2 / FAPbBr3 prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 2.

[0059] Fig.15 This is a photocatalytic hydrogen production cycle stability diagram of 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 of the present invention.

[0060] Fig.16 This is a photocatalytic hydrogen production activity diagram of MoS2, 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 of the present invention, FAPbBr3-0.9 / Pt of Comparative Example 1, and FAPbBr3-0.9 of Comparative Example 2.

[0061] Fig.17 This is the photocatalytic hydrogen production activity diagram of each MoS2 / FAPbBr3-0.9 prepared in Example 1 and Examples 6 to 11 of the present invention.

[0062] Fig.18 This is the X-ray diffraction diagram of the sample of 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 of the present invention before and after the hydrogen production stability test. DETAILED DESCRIPTION

[0063] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0064] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. In the present invention, the singular forms "a", "said" and "the" used in the embodiments and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0065] In an embodiment of the present invention, a method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide comprises the following steps:

[0066] S1. Synthesis of halogenated formamidine: adding acetic acid formamidine to a hydrohalic acid solution for ultrasonic dispersion and then heating and stirring for reaction, then removing the solvent, washing and drying to obtain halogenated formamidine;

[0067] S2, preparation of formamidinium lead halide perovskite and saturated mixed acid solution: adding the excess formamidinium halide and lead halide obtained in step S1 to a mixed acid solution composed of a hydrohalic acid and a hypophosphorous acid solution, heating and stirring the mixture for reaction, cooling the mixture, and centrifuging the mixture for solid-liquid separation to obtain formamidinium lead halide perovskite and a saturated mixed acid solution;

[0068] S3, preparation of molybdenum disulfide: adding molybdate and sulfur source into water, stirring and dissolving, carrying out hydrothermal reaction, centrifuging, washing and drying to obtain molybdenum disulfide;

[0069] S4. Synthesis of photocatalytic material: Add the lead guanidine halide perovskite synthesized in step S2 and the molybdenum disulfide prepared in step S3 to the saturated mixed acid solution obtained in step S2 for heating and stirring reaction, and then cool, centrifuge and dry to obtain the FAPbX3 / MoS2 photocatalytic material, which is the lead-rich halide perovskite bonded with molybdenum disulfide photocatalytic material.

[0070] The saturated mixed acid solution obtained in step S2 is a mixed acid solution in which formamidinium lead halide perovskite is saturated with the solution.

[0071] A method for synthesizing a photocatalytic material of a lead-rich halide perovskite bonded with molybdenum disulfide in the embodiment, by adjusting the ratio of the synthetic raw materials of formamidine halide, lead halide and mixed acid solution, using a saturated solution coprecipitation method to synthesize formamidine lead halide perovskite with rich lead sites on the surface, and then exposing the rich lead sites on the surface of the formamidine lead halide perovskite to closely contact with the sulfur ions in the co-catalyst molybdenum disulfide, and bond to form a stable lead-sulfur bond, the formed strong chemical bond on the interface greatly promotes the separation and transmission of carriers, so that the synthesized photocatalytic material can achieve efficient photocatalytic decomposition of halogen acid to produce hydrogen. The synthesis method of the photocatalytic material has the advantages of simple preparation method, mild reaction conditions, low cost, and large-scale preparation, and the synthesized photocatalytic material has the advantages of high catalytic activity.

[0072] In some embodiments, in step S1, the mass volume ratio of the acetic acid formamidine to the hydrohalic acid solution is 1 g: (1.5-2) mL; and / or

[0073] The mass concentration of the hydrohalic acid solution is 45% to 48%; and / or

[0074] The hydrohalic acid solution includes one or a combination of hydrobromic acid or hydroiodic acid.

[0075] In some embodiments, in step S1, the ultrasonic dispersion time is 5 min to 15 min, the heating temperature is 55° C. to 65° C., and the reaction time is 1.5 h to 2.5 h.

[0076] In some embodiments, in step S2, the molar ratio of the formamidine halide to the lead halide is (0.7-0.95):1; and / or

[0077] The mass volume ratio of the halogenated formamidine to the mixed acid solution is (3-10) g: (50-100) mL; and / or

[0078] In the mixed solution of the hydrohalic acid and the hypophosphorous acid solution, the volume ratio of the hydrohalic acid to the hypophosphorous acid solution is 4:(0.5-1); and / or

[0079] The heating temperature is 60° C. to 80° C., and the reaction time is 1 h to 1.5 h.

[0080] In some embodiments, in step S3, the molybdate is sodium molybdate or potassium molybdate, or a combination of both; and / or

[0081] The sulfur source is one or a combination of thioacetamide or thiourea; and / or

[0082] The molar ratio of the molybdate to the sulfur source is 1:(6-8); or / or

[0083] The temperature of the hydrothermal reaction is 180° C. to 220° C., and the time of the hydrothermal reaction is 20 h to 28 h.

[0084] In some embodiments, in step S4, the mass ratio of the formamidinium lead halide perovskite to molybdenum disulfide is (2.5-100):1; and / or

[0085] The mass concentration of the formamidinium lead halide perovskite in the saturated mixed acid solution is 1 g / L to 4 g / L; and / or

[0086] The temperature of the heating reaction is 50° C. to 80° C., and the reaction time is 1.5 h to 2.5 h.

[0087] In an embodiment of the present invention, a lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic material is prepared by the above-mentioned method for synthesizing a lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic material.

[0088] A photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide in an embodiment of the present invention has the advantages of efficient charge separation, abundant hydrogen production active sites, and small hydrohalic acid splitting energy barrier, and can achieve efficient and stable photocatalytic hydrogen production, with an optimal hydrogen production performance of up to 14000 μmol g -1 h -1 , while having excellent stability.

[0089] In an embodiment of the present invention, a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide is used in the photocatalytic decomposition of halogen acid to produce hydrogen.

[0090] The photocatalytic material can be used for photocatalytic hydrogen production and has efficient and stable photocatalytic hydrogen production activity.

[0091] In an embodiment of the present invention, a method for photocatalytically decomposing halogen acid to produce hydrogen is a method for photocatalytically decomposing halogen acid to produce hydrogen using the above-mentioned lead-rich halide perovskite bonded molybdenum disulfide photocatalytic material, comprising the following steps: dispersing the photocatalytic material in the saturated mixed acid solution, vacuuming to remove air, and using a xenon lamp as a light source to photocatalytically decompose the halogen acid in the saturated mixed acid solution to produce hydrogen.

[0092] In some embodiments, the mass volume ratio of the photocatalytic material to the saturated mixed acid solution is (1-5) mg: 1 mL; and / or

[0093] The power of the xenon lamp is 250W to 350W. The xenon lamp is equipped with filters of AM 1.5 and 420<λ<780nm.

[0094] The following describes the invention in conjunction with specific embodiments.

[0095] Example 1

[0096] A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide comprises the following steps:

[0097] S1. Synthesis of halogenated formamidine: 10 g of acetic acid formamidine was added to 18 mL of hydrobromic acid solution (48 wt % aqueous solution) for ultrasonic dispersion for 10 min, and then heated to 60° C. and stirred for reaction for 2 h. The product was then placed in a rotary evaporator at 60° C. to remove the solvent by rotary evaporation to obtain a crude product. The crude product was then recrystallized three times using ethanol and ether solutions in sequence, and then washed three times with ether, and finally dried in a vacuum oven at 50° C. for 6 h to obtain a white powder product, i.e., formamidine bromide (FABr);

[0098] S2. Preparation of formamidinium lead halide perovskite and saturated mixed acid solution: 18 mmol of formamidinium bromide and 20 mmol of lead bromide (PbBr2) were added to a mixed acid solution consisting of 40 mL of hydrobromic acid and 10 mL of hypophosphorous acid solution, and heated to 80°C. After stirring for 1 hour to reach dynamic equilibrium, the mixture was naturally cooled to room temperature, centrifuged for solid-liquid separation, and the precipitate obtained after centrifugation was placed in a vacuum oven at 60°C and dried for 12 hours to obtain an orange powder product, namely formamidinium lead halide perovskite (denoted as FAPbBr3-0.9), and a saturated solution of formamidinium lead halide perovskite in mixed acid was obtained, namely a saturated mixed acid solution;

[0099] S3. Preparation of molybdenum disulfide: 2 mmol of Na2MoO4 and 12 mmol of thioacetamide were added to a reactor containing 30 mL of deionized water and stirred to dissolve for 2 h, and then subjected to a hydrothermal reaction in an oven at 200°C for 24 h to obtain a crude MoS2 product. The crude MoS2 product was washed alternately with water and ethanol for 3 times, centrifuged and dried in a vacuum oven at 60°C for 12 h to obtain a black powder product of molybdenum disulfide;

[0100] S4. Synthesis of photocatalytic material: Add 100 mg of formamidinium lead halide perovskite synthesized in step S2 and 20 mg of molybdenum disulfide obtained in step S3 to 50 mL of saturated mixed acid solution obtained in step S2, heat to 60°C and stir to react for 2 hours, then cool to room temperature while stirring, then collect the precipitate by centrifugation, and dry the precipitate in a vacuum oven at 60°C for 12 hours to obtain a brown powder product FAPbX3 / MoS2 photocatalytic material, which is the lead-rich halide perovskite bonded with molybdenum disulfide photocatalytic material (denoted as 20% MoS2 / FAPbBr3-0.9).

[0101] Example 2

[0102] A method for synthesizing a photocatalytic material of a lead-rich halide perovskite bonded to molybdenum disulfide, the difference between this embodiment and embodiment 1 is that the amounts of formamidine bromide (FABr) and lead bromide (PbBr2) added are 14 mmol and 20 mmol, respectively, the synthesized formamidine lead halide perovskite is recorded as FAPbBr3-0.7, and the photocatalytic material of the lead-rich halide perovskite bonded to molybdenum disulfide obtained after loading MoS2 is recorded as 20% MoS2 / FAPbBr3-0.7. The remaining components and preparation method are the same as those in embodiment 1.

[0103] Example 3

[0104] A method for synthesizing a photocatalytic material of a lead-rich halide perovskite bonded to molybdenum disulfide, the difference between this embodiment and embodiment 1 is that the amounts of formamidine bromide (FABr) and lead bromide (PbBr2) added are 16 mmol and 20 mmol, respectively, the synthesized formamidine lead halide perovskite is recorded as FAPbBr3-0.8, and the photocatalytic material of the lead-rich halide perovskite bonded to molybdenum disulfide obtained after loading MoS2 is recorded as 20% MoS2 / FAPbBr3-0.8. The remaining components and preparation method are the same as those in embodiment 1.

[0105] Example 4

[0106] A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded to molybdenum disulfide, the difference between this embodiment and embodiment 1 is that the amounts of formamidine bromide (FABr) and lead bromide (PbBr2) added are 17 mmol and 20 mmol, respectively, the synthesized formamidine lead halide perovskite is recorded as FAPbBr3-0.85, and the photocatalytic material of lead-rich halide perovskite bonded to molybdenum disulfide obtained after loading MoS2 is recorded as 20% MoS2 / FAPbBr3-0.85. The remaining components and preparation method are the same as those in embodiment 1.

[0107] Example 5

[0108] A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded to molybdenum disulfide, the difference between this embodiment and embodiment 1 is that the amounts of formamidine bromide (FABr) and lead bromide (PbBr2) added are 19 mmol and 20 mmol, respectively, the synthesized formamidine lead halide perovskite is recorded as FAPbBr3-0.95, and the photocatalytic material of lead-rich halide perovskite bonded to molybdenum disulfide obtained after loading MoS2 is recorded as 20% MoS2 / FAPbBr3-0.95. The remaining components and preparation method are the same as those in embodiment 1.

[0109] Example 6

[0110] A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, the difference between this embodiment and embodiment 1 is that 3 mg of MoS2 is added to the saturated mixed acid solution, and the obtained photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide is recorded as 3% MoS2 / FAPbBr3-0.9. The remaining components and preparation method are the same as those in embodiment 1.

[0111] Example 7

[0112] A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, the difference between this embodiment and embodiment 1 is that 5 mg of MoS2 is added to the saturated mixed acid solution, and the obtained photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide is recorded as 5% MoS2 / FAPbBr3-0.9. The remaining components and preparation method are the same as those in embodiment 1.

[0113] Example 8

[0114] A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, the difference between this embodiment and embodiment 1 is that 10 mg of MoS2 is added to the saturated mixed acid solution, and the obtained photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide is recorded as 10% MoS2 / FAPbBr3-0.9. The remaining components and preparation method are the same as those in embodiment 1.

[0115] Example 9

[0116] A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, the difference between this embodiment and embodiment 1 is that 15 mg of MoS2 is added to the saturated mixed acid solution, and the obtained photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide is recorded as 15% MoS2 / FAPbBr3-0.9. The remaining components and preparation method are the same as those in embodiment 1.

[0117] Example 10

[0118] A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, the difference between this embodiment and embodiment 1 is that 30 mg of MoS2 is added to the saturated mixed acid solution, and the obtained photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide is recorded as 30% MoS2 / FAPbBr3-0.9. The remaining components and preparation method are the same as those in embodiment 1.

[0119] Embodiment 11

[0120] A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, the difference between this embodiment and embodiment 1 is that 40 mg of MoS2 is added to the saturated mixed acid solution, and the obtained photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide is recorded as 40% MoS2 / FAPbBr3-0.9. The remaining components and preparation method are the same as those in embodiment 1.

[0121] Example 12

[0122] A method for synthesizing a lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic material, the difference between this embodiment and embodiment 1 is that 1 mg of MoS2 is added to the saturated mixed acid solution, and the obtained lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic material is recorded as 1% MoS2 / FAPbBr3-0.9. The remaining components and preparation method are the same as those in embodiment 1.

[0123] Example 13

[0124] A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, the difference between this embodiment and embodiment 1 is that the amount of formamidine acetate used in step S1 is 12g; the mass concentration of the hydrobromic acid solution is 45%; in step S1, after ultrasonic dispersion for 5min, it is heated to 55°C and stirred for reaction for 2.5h; in step S2, the mass volume ratio of formamidine halide to mixed acid solution is 3g:100mL, the volume ratio of hydrohalic acid and hypophosphorous acid solution is 4:0.5, the heating temperature is 60°C, and the reaction time is 1.5h; in step S3, the molar ratio of molybdate and sulfur source is 1:7, the temperature of the hydrothermal reaction is 180°C, and the hydrothermal reaction time is 28h; in step S4, the mass concentration of formamidine lead halide perovskite in the saturated mixed acid solution is 1g / L, the heating reaction temperature is 50°C, and the reaction time is 2.5h.

[0125] The remaining components and preparation method are the same as those in Example 1.

[0126] Embodiment 14

[0127] A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, the difference between this embodiment and embodiment 1 is that the amount of acetic acid formamidine in step S1 is 9g; hydroiodic acid solution is used to replace hydrobromic acid solution, and the mass concentration of hydroiodic acid solution is 47%; in step S1, ultrasonic dispersion is performed for 15min and then heated to 65°C, and stirred for reaction for 1.5h; in step S2, the mass volume ratio of halogenated formamidine to mixed acid solution is 10g:50mL, and the hydrohalic acid is 47%; The volume ratio of the solution to the hypophosphorous acid is 4:0.8, the heating temperature is 70°C, and the reaction time is 1.3h; in step S3, sodium molybdate is replaced by potassium molybdate, thioacetamide is replaced by thiourea, the molar ratio of molybdate to the sulfur source is 1:8, the temperature of the hydrothermal reaction is 220°C, and the hydrothermal reaction time is 20h; in step S4, the mass concentration of formamidinium lead halide perovskite in the saturated mixed acid solution is 4g / L, the heating reaction temperature is 80°C, and the reaction time is 1.5h.

[0128] The remaining components and preparation method are the same as those in Example 1.

[0129] Embodiment 15

[0130] Application of a lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic material in photocatalytic decomposition of halogen acid to produce hydrogen. Specifically, a method for photocatalytic decomposition of halogen acid to produce hydrogen is a method for photocatalytic decomposition of halogen acid to produce hydrogen using any one of the lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic materials in Examples 1 to 14, comprising the following steps: dispersing the photocatalytic material in a saturated mixed acid solution, vacuuming to remove air, and using a xenon lamp as a light source to photocatalytically decompose the halogen acid in the saturated mixed acid solution to produce hydrogen.

[0131] In this embodiment, the mass volume ratio of the photocatalytic material to the saturated mixed acid solution is 3 mg:1 mL; the power of the xenon lamp is 300 W, and the xenon lamp is equipped with filters of AM 1.5 and 420<λ<780 nm.

[0132] Example 16

[0133] A method for producing hydrogen by photocatalytic decomposition of halogen acid. The difference between this embodiment and embodiment 15 is that the mass volume ratio of the photocatalytic material to the saturated mixed acid solution is 1 mg:1 mL; the power of the xenon lamp is 250W.

[0134] Embodiment 17

[0135] A method for producing hydrogen by photocatalytic decomposition of halogen acid. The difference between this embodiment and embodiment 15 is that the mass volume ratio of the photocatalytic material to the saturated mixed acid solution is 5 mg:1 mL; the power of the xenon lamp is 350W.

[0136] Comparative Example 1

[0137] A method for synthesizing a lead-rich halide perovskite bonded with molybdenum disulfide photocatalytic material. The difference between this comparative example and Example 1 is that the amounts of formamidinium bromide (FABr) and lead bromide (PbBr2) added are 20 mmol and 20 mmol respectively. The synthesized formamidinium lead halide perovskite is recorded as FAPbBr3-1.0, and the lead-rich halide perovskite bonded with molybdenum disulfide photocatalytic material obtained after loading MoS2 is recorded as 20% MoS2 / FAPbBr3-1.0.

[0138] Comparative Example 2

[0139] A method for synthesizing a lead-rich halide perovskite bonded with molybdenum disulfide photocatalytic material. The difference between this comparative example and Example 1 is that the amounts of formamidinium bromide (FABr) and lead bromide (PbBr2) added are 24 mmol and 20 mmol, respectively. The synthesized formamidinium lead halide perovskite is recorded as FAPbBr3-1.2, and the lead-rich halide perovskite bonded with molybdenum disulfide photocatalytic material obtained after loading MoS2 is recorded as 20% MoS2 / FAPbBr3-1.2.

[0140] Comparative Example 3

[0141] A method for synthesizing a Pt-loaded photocatalytic material, the difference between this comparative example and Example 1 is that the co-catalyst molybdenum disulfide is not loaded through a strong lead-sulfur bond, but is replaced by a loaded Pt catalyst, specifically comprising the following steps:

[0142] S1. Synthesis of halogenated formamidine: 10 g of acetic acid formamidine was added to 18 mL of hydrobromic acid solution (48 wt % aqueous solution) for ultrasonic dispersion for 10 min, and then heated to 60° C. and stirred for reaction for 2 h. The product was then placed in a rotary evaporator at 60° C. to remove the solvent by rotary evaporation to obtain a crude product. The crude product was then recrystallized three times using ethanol and ether solutions in sequence, and then washed three times with ether, and finally dried in a vacuum oven at 50° C. for 6 h to obtain a white powder product, i.e., formamidine bromide (FABr);

[0143] S2. Preparation of formamidinium lead halide perovskite and saturated mixed acid solution: 18 mmol of formamidinium bromide and 20 mmol of lead bromide (PbBr2) were added to a mixed acid solution consisting of 40 mL of hydrobromic acid and 10 mL of hypophosphorous acid solution, and heated to 80°C. After stirring for 1 hour to reach dynamic equilibrium, the mixture was naturally cooled to room temperature, centrifuged for solid-liquid separation, and the precipitate obtained after centrifugation was placed in a vacuum oven at 60°C and dried for 12 hours to obtain an orange powder product, namely formamidinium lead halide perovskite (denoted as FAPbBr3-0.9), and a saturated solution of formamidinium lead halide perovskite in mixed acid was obtained, namely a saturated mixed acid solution;

[0144] S3. Synthesis of photocatalytic material: 100 mg of formamidinium lead halide perovskite (FAPbBr3-0.9) synthesized in step S2 was added to 50 mL of the saturated mixed acid solution obtained in step S2 and stirred for 30 min to disperse evenly to obtain a dispersion, then 5 mg of H2PtCl6·6H2O was added to the dispersion and stirred for 30 min, followed by illumination under a 300 W xenon lamp (visible spectrum) for 2 h for photoreduction, the precipitate was collected by centrifugation, and the precipitate was placed in a vacuum oven at 60°C and dried for 12 h to obtain a dark orange powder product FAPbBr3-0.9 / Pt photocatalytic material (referred to as FAPbBr3-0.9 / Pt).

[0145] Comparative Example 4

[0146] A method for synthesizing a photocatalytic material, the difference between this comparative example and Example 1 is that only steps S1 and S2 are performed to obtain formamidinium lead halide perovskite, specifically comprising the following steps:

[0147] S1. Synthesis of halogenated formamidine: 10 g of acetic acid formamidine was added to 18 mL of hydrobromic acid solution (48 wt % aqueous solution) for ultrasonic dispersion for 10 min, and then heated to 60° C. and stirred for reaction for 2 h. The product was then placed in a rotary evaporator at 60° C. to remove the solvent by rotary evaporation to obtain a crude product. The crude product was then recrystallized three times using ethanol and ether solutions in sequence, and then washed three times with ether, and finally dried in a vacuum oven at 50° C. for 6 h to obtain a white powder product, i.e., formamidine bromide (FABr);

[0148] S2. Preparation of formamidinium lead halide perovskite and saturated mixed acid solution: 18 mmol of formamidinium bromide and 20 mmol of lead bromide (PbBr2) were added to a mixed acid solution consisting of 40 mL of hydrobromic acid and 10 mL of hypophosphorous acid solution, and heated to 80°C. After stirring for 1 hour to reach dynamic equilibrium, the mixture was naturally cooled to room temperature, centrifuged for solid-liquid separation, and the precipitate obtained after centrifugation was placed in a vacuum oven at 60°C and dried for 12 hours to obtain an orange powder product, namely formamidinium lead halide perovskite (denoted as FAPbBr3-0.9), and a saturated solution of formamidinium lead halide perovskite in mixed acid was obtained, namely a saturated mixed acid solution;

[0149] Structural morphology characterization

[0150] (I) Crystal structure characterization by X-ray powder diffraction

[0151] (1) The lead guanidine halide perovskites prepared in Examples 1 to 5 were subjected to X-ray powder diffraction tests respectively. The test results are as follows: Figure 1 As shown. Figure 1 It can be seen from the X-ray diffraction spectrum that the FAPbBr3-0.9 with a lead-rich layer synthesized when the FABr:PbBr2 (molar ratio of formamidine bromide to lead bromide) is 0.9:1 has better crystallinity than the FAPbBr3-0.9 without a lead-rich layer synthesized when the FABr:PbBr2 ratio is 1:1. 3- 1.0 The crystal form is consistent, no phase change occurs, and it has good crystallinity.

[0152] (2) X-ray powder diffraction tests were performed on FAPbBr3-0.9, MoS2, and 20% MoS2 / FAPbBr3-0.9 prepared in Example 1. The test results are as follows: Figure 5 As shown. Figure 5 It can be seen that the X-ray powder diffraction pattern shows that the 20% MoS2 / FAPbBr3-0.9 generated after FAPbBr3-0.9 is loaded with MoS2 does not undergo peak shift and maintains the original crystal form unchanged.

[0153] (II) UV-Vis absorption spectroscopy characterization

[0154] (1) The lead guanidine halide perovskites prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to UV-visible absorption spectrum test and analysis. The test results are as follows: Figure 2 As shown. Figure 2It can be seen that the formamidinium lead halide perovskites obtained in Examples 1 to 3 and Comparative Examples 1 to 2 all have absorption edges at 570nm, and the absorption edges of each material remain unchanged. When the molar ratio of formamidinium bromide to lead bromide is 0.8:1, 0.9:1, and 1:1, the formamidinium lead halide perovskite has a stronger absorption intensity in the visible near-ultraviolet region; and when the molar ratio of formamidinium bromide to lead bromide is 0.7:1 and 1.2:1, the absorption intensity is lower. This is because an appropriate amount of lead bromide does not affect the light absorption of the perovskite; and an excessive amount of lead bromide forms a lead-rich layer on the surface of the perovskite that is too thick, which will reduce the light absorption of the material. In addition, when the formamidinium bromide is excessive, the intrinsic absorption of the synthesized formamidinium lead halide perovskite is poor.

[0155] (2) The FAPbBr3-0.9, MoS2, and 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 were subjected to UV-visible absorption spectrum test and analysis. The test results are as follows: Figure 6 As shown. Figure 6 It can be seen that the absorption edge of 20% MoS2 / FAPbBr3-0.9 generated by FAPbBr3-0.9 after loading MoS2 remains unchanged compared with the original FAPbBr3-0.9, and the light absorption of the photocatalytic material 20% MoS2 / FAPbBr3-0.9 in the near-infrared visible light region is effectively improved. In addition, from the appearance, the color of FAPbBr3-0.9 changes from orange to brown after loading MoS2.

[0156] (III) Morphological characterization by scanning electron microscopy

[0157] The FAPbBr3-0.9 prepared in Example 1 was characterized by scanning electron microscopy. The test results are as follows: Figure 7 The 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 was characterized by scanning electron microscopy, and the test results are as follows Figure 8 As shown. Figure 7 and Figure 8 It can be seen that FAPbBr3-0.9 is in the shape of a quasi-spherical dodecahedron with a particle size of 40 to 60 μm. After loading MoS2, the particle size of 20% MoS2 / FAPbBr3-0.9 is reduced to a certain extent, but the morphology remains the same. Figure 8 It can be seen that MoS2 is evenly distributed on FAPbBr3-0.9, forming a uniform and stable 20% MoS2 / FAPbBr3-0.9.

[0158] (IV) Scanning electron microscope energy scattering element distribution characterization

[0159] (1) The formamidinium lead halide perovskite prepared in Example 1 was subjected to scanning electron microscope energy scattering element distribution detection. The test results are as follows: Figure 4 As shown. Figure 4 It can be seen that the carbon, lead and bromine elements in the prepared formamidinium lead halide perovskite are evenly distributed.

[0160] (2) The 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 was subjected to scanning electron microscope energy scattering element distribution detection. The test results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that the carbon, lead, bromine, molybdenum and sulfur elements are distributed in the prepared 20% MoS2 / FAPbBr3-0.9, indicating that MoS2 is loaded on FAPbBr3 through lead-sulfur bonds.

[0161] (V) Infrared spectroscopy analysis

[0162] The FAPbBr3-0.9, MoS2, and 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 were subjected to infrared spectroscopy tests. The test results are shown in FIG. Fig.10 As shown. Fig.10 It can be seen that the infrared spectrum shows that 20% MoS2 / FAPbBr3-0.9 has three peaks near 476nm, 990nm and 1180nm, corresponding to the vibration of the Pb-S bond, indicating that MoS2 is bonded to FAPbBr3-0.9 through the Pb-S bond. At the same time, Mo-S and SS bond vibrations also occur, indicating that MoS2 is loaded on the surface of FAPbBr3-0.9 through chemical bonding, and therefore has excellent structural stability.

[0163] (VI) Raman spectroscopy analysis

[0164] The FAPbBr3-0.9, MoS2, and 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 were tested by Raman spectroscopy. Fig.11 As shown. Fig.11 It can be seen that the Raman spectrum shows that 20% MoS2 / FAPbBr3-0.9 has three peaks of Pb-S bond vibration near 246nm, 430nm and 720nm, which also shows that MoS2 is bonded to FAPbBr3-0.9 through Pb-S bonds. Therefore, the prepared photocatalytic material has excellent structural stability.

[0165] (VII) X-ray photoelectron spectroscopy analysis

[0166] (1) The FAPbBr3-0.9 and 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 were subjected to X-ray photoelectron spectroscopy to analyze the bromine element. The test results are as follows: Fig.12 As shown. Fig.12It can be seen that the bromine element in the X-ray photoelectron spectrum proves that after FAPbBr3-0.9 is loaded with MoS2, electrons flow from FAPbBr3-0.9 to MoS2, causing the overall movement to higher binding energy.

[0167] (2) The MoS2 and 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 were subjected to X-ray photoelectron spectroscopy to analyze the molybdenum element. The test results are as follows: Fig.13 As shown. Fig.13 It can be seen that the molybdenum element in the X-ray photoelectron spectrum shows that MoS2 obtains electrons after being loaded on FAPbBr3-0.9 and moves toward lower binding energy as a whole.

[0168] (VIII) Electromotive force analysis

[0169] The lead guanidine halide perovskites prepared in Examples 1 to 3 and Comparative Examples 1 to 2 and the molybdenum disulfide prepared in Example 1 were tested for their zeta potential performance. Figure 3 As shown. Figure 3 It can be seen that the positive potential of the formamidine lead halide perovskite prepared in Examples 1 to 3 is improved compared with that in Comparative Example 1, which is due to more positive lead ions on the surface of the material. Therefore, it is shown that when the molar ratio of formamidine bromide to lead bromide in Examples 1 to 3 is 0.9:1, 0.7:1, and 0.8:1, compared with the molar ratio of formamidine bromide to lead bromide in Comparative Example 1 of 1:1, the material surface has abundant lead sites.

[0170] In addition, the positive potential of the lead guanidine halide perovskite prepared in Examples 1 to 3 is greatly improved compared with that of Comparative Example 2 and all show positive charge, while MoS2 shows strong negative charge. That is, the potential drop of Comparative Example 2 is caused by the presence of more bromide ions in the material. Therefore, when the molar ratio of lead guanidine bromide to lead bromide in Comparative Example 2 is 1.2:1, the potential of the lead guanidine halide perovskite prepared will drop. At the same time, MoS2 shows strong negative charge, which indicates that lead guanidine halide perovskite can be self-assembled into a composite material with MoS2 through electrostatic self-assembly.

[0171] Performance Testing

[0172] (I) Determination of photocatalytic hydrogen production activity

[0173] Photocatalytic decomposition of HBr to produce hydrogen test: The photocatalytic reaction is carried out in a glass reaction cell with a quartz cover, which is connected to a closed gas circulation and vacuum system. A circulating cooling water (20°C) is connected below to maintain a constant temperature during the reaction. The top irradiation light source uses a 300W xenon lamp to simulate sunlight (AM1.5, 420<λ<780nm, 100mW / cm 2). Take 50 mg of photocatalytic material and put it into 50 mL of the corresponding saturated mixed acid reaction solution, stir and evacuate for 30 minutes to ensure that the air in the reactor is completely removed. Analyze the separated gas by the connected gas chromatography, and set it to automatically sample once every 30 minutes of illumination; in the cycle test, every 5 hours is a cycle, and the system is re-evacuated to start the test.

[0174] The 20% MoS2 / FAPbBr3 prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for photocatalytic hydrogen production activity. Fig.14 As shown. Fig.14 It can be seen that under the current test conditions, the photocatalytic material 20% MoS2 / FAPbBr3 prepared in Example 1 has the best hydrogen production activity, which is 14000 μmol / g / h.

[0175] In addition, the photocatalytic material 20% MoS2 / FAPbBr3 prepared in Example 1 was used to carry out a photocatalytic hydrogen production cycle stability test. The test results of the photocatalytic hydrogen production cycle stability are as follows: Fig.15 As shown. Fig.15 It can be seen that the photocatalytic material 20% MoS2 / FAPbBr3 prepared in Example 1 has good photocatalytic stability.

[0176] In addition, the 20% MoS2 / FAPbBr3-0.9, MoS2 prepared in Example 1, the FAPbBr3-0.9 / Pt sample prepared in Comparative Example 3 and the FAPbBr3-0.9 sample prepared in Comparative Example 4 were tested for photocatalytic hydrogen production activity and the test results are shown in FIG. Fig.16 As shown. Fig.16 It can be seen that the 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 has the best hydrogen production activity. It can be seen that the lead-rich halide perovskite bonded molybdenum disulfide photocatalytic material prepared in the present invention has better hydrogen production activity than the Pt-loaded photocatalytic material prepared in Comparative Example 3.

[0177] In addition, the photocatalytic hydrogen production activity of each MoS2 / FAPbBr3-0.9 sample prepared in Example 1 and Examples 6 to 11 was tested and compared. The test results are as follows: Fig.17 As shown. Fig.17 It can be seen that the photocatalytic material 20% MoS2 / FAPbBr3-0.9 prepared in Example 1 has the best hydrogen production performance. It can be seen that the photocatalytic material prepared when the mass ratio of formamidinium lead halide perovskite and molybdenum disulfide is 5:1 has the best hydrogen production performance.

[0178] (II) Photocatalytic stability test

[0179] The 20% MoS2 / FAPbBr3-0.9 sample prepared in Example 1 was tested for stability by X-ray powder diffraction before and after photocatalytic hydrogen production. The test results are as follows: Fig.18 As shown. Fig.18 It can be seen that the structure of the photocatalytic material prepared by the present invention does not change after catalytic hydrogen production compared with before catalytic hydrogen production, which proves that the photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide prepared by the present invention not only has a strong surface interface effect, but also has good photocatalytic stability.

[0180] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, characterized in that: The following steps are involved: S1. Synthesis of halogenated formamidine: adding acetic acid formamidine to a hydrohalic acid solution for ultrasonic dispersion and then heating and stirring for reaction, then removing the solvent, washing and drying to obtain halogenated formamidine; S2. Preparation of formamidinium lead halide perovskite and saturated mixed acid solution: adding excess formamidinium halide and lead halide to a mixed acid solution composed of hydrohalic acid and hypophosphorous acid solution, heating and stirring to react, cooling, and centrifuging to separate solid and liquid to obtain formamidinium lead halide perovskite and a saturated mixed acid solution; S3, preparation of molybdenum disulfide: adding molybdate and sulfur source into water, stirring and dissolving, carrying out hydrothermal reaction, centrifuging, washing and drying to obtain molybdenum disulfide; S4. Synthesis of photocatalytic material: Add the lead guanidine halide perovskite synthesized in step S2 and the molybdenum disulfide prepared in step S3 to the saturated mixed acid solution obtained in step S2 for heating and stirring reaction, and then cool, centrifuge and dry to obtain the FAPbX3 / MoS2 photocatalytic material, which is the lead-rich halide perovskite bonded with molybdenum disulfide photocatalytic material.

2. The method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide according to claim 1, characterized in that: In the step S1, the mass volume ratio of the acetic acid formamidine to the hydrohalic acid solution is 1 g: (1.5-2) mL; and / or The mass concentration of the hydrohalic acid solution is 45% to 48%; and / or The hydrohalic acid solution includes one or a combination of hydrobromic acid or hydroiodic acid.

3. The method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide according to claim 1, characterized in that: In the step S1, the ultrasonic dispersion time is 5 min to 15 min, the heating temperature is 55° C. to 65° C., and the reaction time is 1.5 h to 2.5 h.

4. The method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide according to claim 1, characterized in that: In the step S2, the molar ratio of the formamidine halide to the lead halide is (0.7-0.95):1; and / or The mass volume ratio of the halogenated formamidine to the mixed acid solution is (3-10) g: (50-100) mL; and / or In the mixed solution of the hydrohalic acid and the hypophosphorous acid solution, the volume ratio of the hydrohalic acid to the hypophosphorous acid solution is 4:(0.5-1); and / or The heating temperature is 60° C. to 80° C., and the reaction time is 1 h to 1.5 h.

5. The method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide according to claim 1, characterized in that: In step S3, the molybdate is sodium molybdate or potassium molybdate, or a combination of both; and / or The sulfur source is one or a combination of thioacetamide or thiourea; and / or The molar ratio of the molybdate to the sulfur source is 1:(6-8); or / or The temperature of the hydrothermal reaction is 180° C. to 220° C., and the time of the hydrothermal reaction is 20 h to 28 h.

6. The method for synthesizing a photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide according to claim 1, characterized in that: In the step S4, the mass ratio of the formamidinium lead halide perovskite to molybdenum disulfide is (2.5-100):1; and / or The mass concentration of the formamidinium lead halide perovskite in the saturated mixed acid solution is 1 g / L to 4 g / L; and / or The temperature of the heating reaction is 50° C. to 80° C., and the reaction time is 1.5 h to 2.5 h.

7. A photocatalytic material of lead-rich halide perovskite bonded with molybdenum disulfide, characterized in that: The photocatalytic material is prepared by the synthesis method of a lead-rich halide perovskite bonded with molybdenum disulfide as described in any one of claims 1 to 6.

8. Use of the lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic material as claimed in claim 7 in photocatalytic decomposition of halogen acid to produce hydrogen.

9. A method for producing hydrogen by photocatalytic decomposition of halogen acid, characterized in that: The method is a method for photocatalytically decomposing halogen acid to produce hydrogen using the lead-rich halide perovskite-bonded molybdenum disulfide photocatalytic material described in claim 7, comprising the following steps: dispersing the photocatalytic material in the saturated mixed acid solution, vacuuming to remove air, and using a xenon lamp as a light source to photocatalytically decompose the halogen acid in the saturated mixed acid solution to produce hydrogen.

10. A method for producing hydrogen by photocatalytic decomposition of halogen acid as claimed in claim 9, characterized in that: The mass volume ratio of the photocatalytic material to the saturated mixed acid solution is (1-5) mg: 1 mL; and / or The power of the xenon lamp is 250W-350W.

Citation Information

Patent Citations

  • Preparation method of methylamine lead iodine-reduced graphene oxide composite photocatalytic material and application in photocatalytic hydrogen production by using the photocatalytic material

    CN107876087A

  • Molybdenum disulfide / formamidinium lead bromate composite photocatalyst, and preparation method and applications thereof

    CN110465332A

  • MAPbI3 perovskite-based composite photocatalyst as well as preparation method and application thereof

    CN114471717A